Sosialisasi Pengenalan Pendidikan dalam Meningkatkan Kesadaran Masyarakat Desa Tambak Ukir Terhadap Pentingnya Pendidikan di Masa Depan - Siti Seituni; Ida Fitriana Ambarsari; Nur Hasanah; Nur Afia (I-Com: Indonesian Community Journal, 2023)
Community service activities in the form of providing motivation and showing videos related to the importance of education and being educated in the future have the aim of increasing community awareness, especially in Tambak Ukir village, Kendit district. This activity was carried out at SDN 1 Tambak Ukir with a total of 44 participants. The method used in this community service activity is an introduction to the aims and objectives of the activity, followed by an expository method, namely delivering the material and closing with an evaluation of the material, namely giving quizzes and prizes to participants. Furthermore, the results of this community service activity can be seen from several criteria, namely achieving the target number of service participants, achieving the goals of the service, and the participants' ability to understand the material and the benefits of community service activities. Based on the results of several criteria, it is known that all criteria were achieved with very good results.